Frequent Questions about our Solver

The problem

Click to see the original problem

Please explain how the binomials end up with both negative. I am thinking its the implied -1 again that is multiplied through the 3y(-x+6y).

Thank you, love your website, and customer service is great.

Answer provided by our tutors

If you want to see more steps, you can go to 'Options' tab and select 'Show: a lot of steps'.

This way, you will get the following additional steps that explain how we get the resulting binomials:

So, -1 comes from dividing (- x + 6y) by (x - 6y):

(- x + 6y) / (x - 6y) = 

= (-1)(x - 6y) / (x - 6y) = 

= -1

← Previous Problem Next Problem →